2003
DOI: 10.1074/jbc.m213091200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Protease-activated Receptor-4 Actions in Cardiomyocytes

Abstract: Protease-activated receptor (PAR)-4 is a low affinity thrombin receptor with slow activation and desensitization kinetics relative to PAR-1. This study provides novel evidence that cardiomyocytes express functional PAR-4 whose signaling phenotype is distinct from PAR-1 in cardiomyocytes. AYPGKF, a modified PAR-4 agonist with increased potency at PAR-4, activates p38-mitogenactivated protein kinase but is a weak activator of phospholipase C, extracellular signal-regulated kinase, and cardiomyocyte hypertrophy; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
1
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 25 publications
3
65
1
1
Order By: Relevance
“…This may be an artifact due to the immunoblotting steps because EGF-R was detected at similar levels when the immunoblot was probed directly with anti-EGF-R after immunoprecipitation (data not shown). It is suggested that the high signal with the anti-phosphotyrosine antibody prevents subsequent anti-EGF-R antibody binding to the EGF-R epitope as observed previously (49). The figure shows representative immunoblots.…”
Section: Activation Of Erks and Cell Proliferation Induced By Par2 Agmentioning
confidence: 65%
“…This may be an artifact due to the immunoblotting steps because EGF-R was detected at similar levels when the immunoblot was probed directly with anti-EGF-R after immunoprecipitation (data not shown). It is suggested that the high signal with the anti-phosphotyrosine antibody prevents subsequent anti-EGF-R antibody binding to the EGF-R epitope as observed previously (49). The figure shows representative immunoblots.…”
Section: Activation Of Erks and Cell Proliferation Induced By Par2 Agmentioning
confidence: 65%
“…Src family kinases previously have been implicated in the cross-talk between EGFR and GPCRs (14,19,35). Activation of Src family kinases, including Fyn, c-Yes, and c-Src, have been reported to be an early event following thrombin treatment in lung fibroblast CCL39 cells (36).…”
Section: Discussionmentioning
confidence: 99%
“…These in vivo data suggest that the Gq-coupled receptor 5-HT (2B) uses the signaling pathway of tyrosine kinase receptor erbB2 for cardiac differentiation (Nebigil et al, 2000). In cardiac myocytes, EGFR kinase activity is involved in protease-activated receptor (PAR)4-dependent (relative of cardiac myocyte G protein-coupled receptors) activation of the p-38 mitogen-activated protein kinase (MAPK) signaling pathway, again showing cross-talk between EGFR and G protein-coupled receptor signaling (Sabri et al, 2003).…”
Section: A the Erbb Signaling Networkmentioning
confidence: 99%